Exosome Therapy from Hypoxia-treated Mesenchymal Stem Cells Reduces TNF-α and Increases VEGF Levels in Fluconazole-Induced Alopecia Model - Sulistami, Siska Marlina; Mulyani, Sri Priyantini; Putra, Agung; Setiawan, Eko (Cell and BioPharmaceutical Institute, 2025)
Background: Alopecia is a condition with partial or complete hair loss, leading to psychological distress. Current treatments, such as minoxidil and finasteride, have limited efficacyand side effects. Recent studies suggest that mesenchymal stem cells (MSCs)-derived exosomes offer regenerative potential by modulating inflammation and enhancing hair follicle regeneration, though optimal dosage remains unclear. Tumor necrosis factor-alpha (TNF-α) inhibits hair follicle growth, while vascular endothelial growth factor (VEGF) promotes hair regrowth. This study evaluates exosome therapy from hypoxia (Hypo-Exo)-treated MSCs in modulating TNF-α and VEGF in a fluconazole-induced alopecia-like model..Materials and methods: An experimental post-test only control group design was used with 30 male Wistar rats, divided into five groups: Healthy group, 0.9% NaCl-treated group, 5% Minoxidil-treated group, 100 μg/mL Hypo-Exo MSCs-treated group, and 200 μg/mL Hypo-Exo MSCs-treated group. TNF-α and VEGF levels were analyzed using ELISA on day 14 post-treatment. Results: The highest TNF-α level was found in the 0.9% NaCl-treated group (307.46 ± 20.68 pg/mL) and significantly reduced (p<0.05) in 100 μg/mL Hypo-Exo MSCs-treated group (65.38±15.05 pg/mL) and 200 μg/mL Hypo-Exo MSCs-treated group (37.16±7.14 pg/mL). VEGF levels were the highest in the 200 μg/mL Hypo-Exo MSCs-treated group (189.11±9.75 pg/mL) and 100 μg/mL Hypo-Exo MSCs-treated group (158.50±5.33 pg/mL), compared to the 0.9% NaCl-treated group (69.60±15.39 pg/mL). Conclusion: Hypo-Exo MSCs significantly reduced TNF-α and increased VEGF levels, supporting their potential as a novel regenerative therapy for alopecia. Keywords: alopecia, TNF-α, VEGF, exosome, hypoxia, mesenchymal stem cells